Stress responses to repeated exposure to a combined physical and social evaluative laboratory stressor in young healthy males. (January 2016) - Boyle, N.B.; Lawton, C.; Arkbåge, K.; West, S.G; Thorell, L.; Hofman, D.; Weeks, A.; Myrissa, K.; Croden, F.; Dye, L.
Highlights: Male stress responses to repeated physical/social-evaluative stress were examined. Stressor exposure significantly increased all stress response parameters. The common cortisol response habituation to repeated exposure was not shown. Potentially useful tool for designs requiring repeated use of a homotypic stressor. Abstract: Repeated exposure to homotypic laboratory psychosocial stressors typically instigates rapid habituation in hypothalamic–pituitary–adrenal (HPA) axis-mediated stress responses in humans. However, emerging evidence suggests the combination of physical stress and social evaluative threat may be sufficient to attenuate this response habituation. Neuroendocrine, cardiovascular and subjective stress responses following repeated exposure to a combined physical and social evaluative stress protocol were assessed to examine the habituation response dynamic in this context. The speech task of the Trier social stress test (TSST;Kirschbaum et al., 1993 ) and the socially evaluated cold pressor task (SECPT;Schwabe et al., 2008 ) were administered in a combined stressor protocol. Salivary cortisol, cardiovascular and subjective stress responses to a non-stress control and repeat stressor exposure separated by six weeks were examined in males ( N  = 24) in a crossover manner. Stressor exposure resulted in significant elevations in all stress parameters. In contrast to the commonly reported habituation in cortisol response, a comparable post-stress response was demonstrated. Cortisol, heart rate and subjective stress responses were also characterised by a heightened response in anticipation to repeated stress exposure. Blood pressure responses were comparatively uniform across repeated exposures. Findings suggest a combined physical and social evaluative stressor is a potentially useful method for study designs that require repeated presentation of a homotypic stressor.